Taisei yochi zusetsu. Kan no 1-3 - Kutsuki, Masatsuna, 1750-1802 (Edo : Matsumoto Zenbē, 2021)
Vol. 1-3 contains a preface by 鳩谷孔平 Hatotani Kōhei and an index. There are 27 maps in vol. 15-17, based on European models; most maps are double-page. Contents: Vol. 1-3. General introduction to Europe, Portugal, Spain -- Vol. 4-5. France, England -- Vol. 6-8. Netherlands, Switzerland, Italy -- Vol. 9-10. Germany, Scandinavia -- Vol. 11-14. Poland, Moscovia (Russia), Hungary, Greece -- Vol. 15-17 maps of Europe, Arctic regions, plans of cities. Cited in: WSN; 110-111 ...